The Effect of Work Environment, Work Facilities and Work Motivation on Employee Performance at the DPRD Secretariat Bondowoso Regency - Abdul Wahet; Suwignyo Widagdo; Agustin Hari Prastyowati (ABM: International Journal of Administration, Business and Management, 2020)
To achieve organizational goals requires a good performance from its employees. Employee performance factors are strongly influenced by the work environment, work facilities and employee motivation. The purpose of this study was to determine how much influence the Work Environment, Work facilities and Work Motivation on Employee Performance in the Secretariat of the Bondowoso Regency DPRD either partially or simultaneously. Respondents in this study were 65 civil servants with civil servant status in the Secretariat of the DPRD Bondowoso Regency as many as 65 people who were determined using saturated sampling techniques, where all populations were sampled. The data analysis used in this study is multiple linear regression analysis to determine the level of influence of the independent variable on the dependent variable with the help of the SPSS for Windows program. The partial test results for the influence of work environment variables on employee performance, it is known that there is a significant influence of work environment on employee performance. For the influence of work facilities variables on employee performance, it is known that there is a significant effect of work facilities on employee performance. And for the influence of work motivation variables on employee performance, it is known that there is a significant effect of work motivation on employee performance. Simultaneous testing results, it can be concluded that the work environment, work facilities, and work motivation are proven to have a significant effect simultaneously on employee performance in the Secretariat of the DPRD Bondowoso Regency. Keywords: Work Environment; Work Facilities; Work Motivation; Employee Performance